The Implementation of Archive Storage for Enhanced Document Retrieval at PT Kusuma Satria Dinasasri Wisatajaya Batu, Indonesia - Maharani, Shinta (ISAS (Indonesian Society of Applied Science), 2024)
This study examines archive storage implementation to facilitate document retrieval at PT Kusuma Satria Dinasasri Wisatajaya Batu's Human Resources Department. It adopts a qualitative approach, employing observation, interviews, and documentation for data collection. The research shows that the way archives are stored isn't as good as it could be. This is demonstrated by problems like insufficient understanding and supervision of archives, no borrowing procedures, archives that keep growing, and a lack of staff that makes retrieval times longer. These challenges significantly impact job performance. Suggestions for improvement include enhancing employees' understanding of the importance of archives and organisational systems. We advise implementing a Record Retention Schedule (RRS) to manage archive accumulation effectively. Addressing space constraints and establishing borrowing procedures with defined periods are essential. Moreover, a monitoring system for archives is crucial to ensure proper organisation and maintenance. In conclusion, optimising archive storage practices is vital for efficient document retrieval and organisational effectiveness. By addressing identified issues and implementing suggested improvements, PT Kusuma Satria Dinasasri Wisatajaya Batu can enhance its archive management processes and support smoother operations in the Human Resources Department.